Taxadb: A high‐performance local taxonomic database interface. Issue 9 (2nd August 2020) - Norman, Kari E. A.; Chamberlain, Scott; Boettiger, Carl
Abstract: A familiar and growing challenge in ecological and evolutionary research is that of establishing consistent taxonomy when combining data from separate sources. While this problem is already well understood and numerous naming authorities have been created to address the issue, most researchers lack a fast, consistent, and intuitive way to retrieve taxonomic names. We present taxadb R package which creates a local database, managed automatically from within R, to provide fast operations on millions of taxonomic names. taxadb provides access to established naming authorities to resolve synonyms, taxonomic identifiers, and hierarchical classification in a consistent and intuitive data format. taxadb makes operation on millions of taxonomic names fast and manageable.